2014
DOI: 10.1007/s10531-014-0750-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional structure of ant and termite assemblages in old growth forest, logged forest and oil palm plantation in Malaysian Borneo

Abstract: Forested tropical landscapes around the world are being extensively logged and converted to agriculture, with serious consequences for biodiversity and potentially ecosystem functioning. Here we investigate associations between habitat disturbance and functional diversity of ants and termites-two numerically dominant and functionally important taxa in tropical rain forests that perform key roles in predation, decomposition, nutrient cycling and seed dispersal. We compared ant and termite occurrence and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 61 publications
(72 reference statements)
12
102
4
1
Order By: Relevance
“…They showed that earthworm density varied with the type of soil and with the age of the plantation. We found a very low termite density in our study (3e4 ind m À2 ) in agreement with Luke et al [39] who showed that termites occurred less frequently in converted habitats such as oil palm plantation than in old growth forest in Malaysia. However, Lavelle et al [4] found a termite density of 2022 ind m À2 in a Colombian oil palm plantation.…”
Section: Soil Biodiversity In Oil Palm Plantationssupporting
confidence: 92%
“…They showed that earthworm density varied with the type of soil and with the age of the plantation. We found a very low termite density in our study (3e4 ind m À2 ) in agreement with Luke et al [39] who showed that termites occurred less frequently in converted habitats such as oil palm plantation than in old growth forest in Malaysia. However, Lavelle et al [4] found a termite density of 2022 ind m À2 in a Colombian oil palm plantation.…”
Section: Soil Biodiversity In Oil Palm Plantationssupporting
confidence: 92%
“…substitution of species). On a local scale, increment of temperature and humidity may also affect negatively the humivorous guild due to greater sensitivity to desiccation (see Eggleton et al, 1994Eggleton et al, , 2002Davies, 2002;Jones et al, 2003;Luke et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Termite species have been shown to be responsive to environmental disturbance (Souza and Brown, 1994;Davies, 2002;Luke et al, 2014). However, mechanisms in which habitat fragmentation alters the community structure of these insects are still poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, soil ecosystem engineers modify and in some instances may determine the major physical, chemical and microbiological properties of the soil [7,8,9,10,11], especially those associated with soil aggregate stability and fertility [10,12]. As social insects with high abundance and biomass [13], and active in nest building and tunneling, termites and ants are hypothesized to deliver a number of services including contribution to organic matter decomposition, nutrient recycling, bioturbation, tilth, porosity and cation exchange capacity [5,14,15,16]. In addition, their consumption or manipulation of organic materials creates biogenic 5 structures [3] that can be significant components of the soil profile, and as they usually comprise mixtures of clay and organic materials, they exist as microsites for biological transformations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because many of these changes lead to a rapid decline in fertility or erosion [13] comparison of the fauna across mosaic landscapes and between different land uses and regions provides both an indirect test of the validity of the soil engineer concept and guidance for future management of cropping systems [19,20,21].…”
Section: Introductionmentioning
confidence: 99%